The role of functioning in predicting nursing home placement or death among older home care patients - Eeva Björkstedt; Ari Voutilainen; Kati Auvinen; Virva Hyttinen; Johanna Jyrkkä; Pekka Mäntyselkä; Eija Lönnroos (Scandinavian Journal of Primary Health Care, 2023)
Objective There have been few studies predicting institutionalization or death in home care settings. We examined risk factors for nursing home placement (NHP) and death among home care patients.Design A prospective one-year follow-up study.Settings and subjects Persons aged ≥65 years living in Eastern Finland and receiving regular home care services (n = 293).Main outcome measures Risk factors for NHP or death were investigated using Cox proportional hazards model. Explanatory variables included demographics, health status (Charlson Comorbidity Index, CCI), physical (Timed Up and Go, TUG), and cognitive (Mini-Mental State Examination, MMSE) functioning, Basic and Instrumental Activities of Daily Living (BADL, IADL) and mood (Geriatric Depression Scale, GDS-15).Results Of the 293 patients (mean age 82.6 years, 70.6% women), 27 (9.2%) moved to a nursing home and 25 (6.9%) died during the follow-up (mean 350 days). The combined outcome of NHP or death was predicted by BADL (HR 0.73, CI 95% 0.62–0.86), IADL (0.75, 0.65–0.87) MMSE (0.92, 0.87–0.96), and TUG (1.02, 1.01–1.03). NHP alone was predicted by BADL (0.62, 0.50–0.78), IADL (0.57, 0.45–0.73), and MMSE (0.88, 0.82–0.94) and mortality by TUG (1.02, 1.01–1.03).Conclusion Basic measures of functioning can be used to identify high-risk patients in home care. Decreasing BADL, IADL and MMSE predict NHP and longer TUG-times death within a year.